Pengaruh Indeks Harga Saham Gabungan, Nilai Tukar Rupiah dan Repo Rate Terhadap Nilai Aktiva Bersih Reksadana Syariah Di Indonesia Periode 2015-2018 - Efrinal - (AKRUAL : Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine the effect of the composite stock price index (CSPI), the exchange rate of the rupiah (KURS), and the repo rate on the net asset value (NAV) of sharia mutual funds in Indonesia in 2015-2018. The sample used in this study is monthly data from January 2015 to December 2018. Hypothesis testing uses time-series data regression analysis. The population in this study is the entire net asset value of sharia mutual funds that are effective and recorded in the Financial Services Authority for the 2015-2018 period. The data used are secondary data with the documentation method. Before analyzing the data, a classic assumption test is held which consists of a normality test, a multicollinearity test, a heteroscedasticity test, and an autocorrelation test. The analytical method used is multiple linear regression analysis. Based on the results of data analysis and discussion, the composite stock price index (CSPI) has a positive and significant effect on the NAV of sharia mutual funds, the rupiah exchange rate (exchange rate) has a positive and significant effect on the Sharia mutual fund NAV, and the repo rate has a negative and insignificant effect on the Sharia mutual fund NAV